Documentation of spinal anaesthesia technique and block level at caesarean section - Du Toit, Michiel Adriaan (Department of Anaesthesia and Perioperative Medicine, 2022)
Background The ease of administration and relative safety of spinal anaesthesia has made this the preferred technique for elective and many emergency caesarean sections. Complications include incomplete sensory block, resulting in intraoperative breakthrough pain, which is commonly associated with a successful medicolegal claim. If documentation of spinal anaesthesia technique was found to be inadequate in the course of such medicolegal proceedings, it is likely that the decision would be against the anaesthetist. The purpose of this study was to evaluate documentation by anaesthetists relating to the establishment of surgical anaesthesia utilizing subarachnoid block. Methods A retrospective folder analysis was conducted at Mowbray Maternity Hospital in Cape Town, South Africa. One hundred consecutive spinal anaesthesia charts, each completed by a different anaesthetist, either a registrar or specialist, were analysed, starting December 31st, 2018, and proceeding retrospectively in time until the sample size was achieved. Results Of the 100 cases of spinal anaesthesia for caesarean section analysed, 68 were emergency and 32 elective operations. After literature review, 12 variables were identified requiring documentation, so that adequate information would be available in the event of medicolegal action. In 23% and 32% of patients respectively, 7 or 8/12 were recorded. Ninety percent of anaesthesia charts had inadequate documentation, defined as information on fewer than 10 of the specified variables. Conclusion The quality of documentation of procedure and block level during spinal anaesthesia for caesarean section was inadequate. National guidelines should be drafted and standardised to improve the quality of these records, both for quality of care and medicolegal purposes.